Efforts to Prevent Human Trafficking through Strengthening Rural Community Economic Empowerment - Nuraeny, Henny; Monaya, Nova; Ma'arif, Rizal Syamsul; Yusuf , Muhammad Arsjad; Norawavi, Ahmad Norsyafwan (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2026)
At present, villages receive funding from the central government to develop their potential and improve the economic welfare of rural communities. However, in practice, the use of village funds (dana desa) has not yet been optimal, leading many villagers to seek employment outside the village and making them vulnerable to human trafficking (Tindak Pidana Perdagangan Orang, or TPPO). This research examines how rural economic empowerment through village funds can prevent human trafficking and explores alternative empowerment models. The research method employed is normative juridical; however, to achieve empirical accuracy and validation, a mixed-methods approach combining qualitative and quantitative techniques was also applied during observation. The study's findings indicate that the optimal allocation of village funds to develop the creative economy through entrepreneurship, cooperatives, and micro, small, and medium enterprises (MSMEs) can strengthen community resilience and reduce migration pressures. This research proposes a model of rural economic empowerment that emphasizes sustainable development and the establishment of village-level regulations to allocate village funds to preventive efforts against human trafficking. The implementation of this model is expected to serve as a reference for village governments in effectively utilizing village funds to address socio-economic vulnerabilities.